Role of BNP and echo measurement for pulmonary hypertension recognition in patients with interstitial lung disease: An algorithm application model. Issue 3 (March 2015) - Ruocco, Gaetano; Cekorja, Behar; Rottoli, Paola; Refini, Rosa Metella; Pellegrini, Marco; Di Tommaso, Cristina; Del Castillo, Gabriele; Franci, Beatrice; Nuti, Ranuccio; Palazzuoli, Alberto
Summary Background This study evaluated the role of echocardiography and BNP in patients with interstitial lung disease (ILD), to identify those with PH and RV dysfunction. The aims of this study were: 1-to evaluate the accuracy of an algorithm including BNP, DLCO and echocardiographic measurements to identify PH and RV dysfunction; 2- to evaluate BNP and Echo values concordance in relation to right catheterization measurement. Methods We analyzed 113 patients with diagnosis of ILD. Echo examination included: Pulmonary systolic, diastolic and mean Arterial Pressure (PAPs, PAPd, PAP mean), End-Diastolic and End-Systolic right ventricle diameters, Inferior Caval Vein diameter, and Tricuspid Annular Plane Systolic Excursion (TAPSE). Patients revealing increased PAPs at echocardiography underwent to catheterization. Results Patients with PAPs > 40 mm Hg (37 patients), PAPmean ≥ 25 mm Hg (23 patients) and PAPd ≥ 20 mm Hg showed BNP increased (157 ± 96 vs 16 ± 14 pg/ml p = 0.004; 201 ± 120 vs 28 ± 17 pg/mL; 124 ± 88 vs 23 ± 18 pg/ml p < 0.001) as patients with TAPSE ≤16 mm (25 patients) (145 ± 104 vs 26 ± 21 pg/ml p < 0.001). In catheterized patients (37 patients) BNP was increased in patients with invasive PAPs > 40 mm Hg (165 ± 112 vs 29 ± 14 pg/ml p < 0.02), as well as in patients with Wedge pressure > 14 mm Hg (199 + 153 vs 54 + 39 pg/mL; p = 0.01). ROC Curve analysis showed that elevated values of BNP, PAPs, PAP mean are able to assess PH. On the other hand, lower values of DLCO (<40%) and TAPSE (≤16 mm) detect PH. Logistic regression analysis of the previous parameters, confirmed their diagnostic role in PH detection. Conclusions In patients with ILD, an algorithm including BNP, DLCO and echocardiography could be useful for non invasive screening of PH. Clinical trial registration name and number : ARTEMIS-HP trial; ID number: NCT00879229.